Economic Valuation of Ecosystems in Shadegan International Wetland, Iran - Kaffashi, Sara (2010)
Shadegan International Wetland is a unique natural ecosystem with great nationaland international significance, designed under Ramsar Convention. Located in southern part of Iran, this wetland bears many functions. Among them the rich biodiversity, ecological, hydrological, and economic functions are most important. Despite the great opportunities for sustainable development of this wetland, it is currently under serious threats from diverse range of non-sustainable activities,particularly those related to water management, irrigation, agriculture and petrochemical industries. One of the major reasons for excessive depletion and conversion of wetland resources is due to underestimate non-market values of wetland in development decisions. The aim of this study is therefore to estimate the economic benefit of Shadegan International Wetland as a very useful instrument to reflect the values of this unique ecosystem to society members. Choice Experiment (CE) and Contingent Valuation Methods (CVM) were employed in the study. In CVM section, willingness to pay (WTP) elicitation format, dichotomous choice and a close ended question was used. In CE part, five categories of non-market value of wetland were defined including: natural environment, biodiversity, water quality, ecological functions and conservation value. A total of 500 respondents were interviewed in person, using stratified random sampling method. In CVM section, the logit model was defined based on dichotomous choice method to estimate the WTP off a specified bid amount to the hypothetical price to support Shadegan International Wetland Conservation. The nested logit model was applied to drive marginal value and compensating surplus of respondents to five attributes of non-market values of Shadegan Wetland. The results demonstrated respondents positive WTP for wetland conservation. The findings also indicated that respondents who had higher income, higher education, small household size, being employed and female were more likely agreed to pay for wetland conservation. The estimated mean for the WTP was 25,398 Rials per household from CE and16,203 RLS per household from CVM. The survey also identified user and nonuser WTP in CVM section, which were 21,083 Rials and 28,402 Rials perhousehold for user and non-user respectively. Since natural resources including wetlands are important part of wealth in each country; thus, the result of this study can provide useful information about goods and services provided by wetland and their value. In this way, the findings can be used for larger societal awareness about the wetlands and wetland-based benefits, including economic benefits. The results of this study could be beneficial to policy makers, authorities such as regional and local managers to better consideration of the consequences of present policies on the real value of wetland services. On the other hand, the results of valuation can help to convince the government and other decision makers to allocate more resources for conservation. By identifying and quantifying the major benefits provided by wetland, the valuation can provide invaluable support to the conservation efforts. Therefore, the benefits of wetland for society based on WTP results could encourage managers to set priorities to ensure that the ecosystem health, integrity and uniqueness would be conserved in proper manner.